Fetal cardiac interventions: clinical and experimental research - Yuan, Shi-Min; Humuruola, Gulimila (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Fetal cardiac interventions for congenital heart diseases may alleviate heart dysfunction, prevent them evolving into hypoplastic left heart syndrome, achieve biventricular outcome and improve fetal survival. Candidates for clinical fetal cardiac interventions are now restricted to cases of critical aortic valve stenosis with evolving hypoplastic left heart syndrome, pulmonary atresia with an intact ventricular septum and evolving hypoplastic right heart syndrome, and hypoplastic left heart syndrome with an intact or highly restrictive atrial septum as well as fetal heart block. The therapeutic options are advocated as prenatal aortic valvuloplasty, pulmonary valvuloplasty, creation of interatrial communication and fetal cardiac pacing. Experimental research on fetal cardiac intervention involves technical modifications of catheter-based cardiac clinical interventions and open fetal cardiac bypass that cannot be applied in human fetuses for the time being. Clinical fetal cardiac interventions are plausible for midgestation fetuses with the above-mentioned congenital heart defects. The technical success, biventricular outcome and fetal survival are continuously being improved in the conditions of the sophisticated multidisciplinary team, equipment, techniques and postnatal care. Experimental research is laying the foundations and may open new fields for catheter-based clinical techniques. In the present article, the clinical therapeutic options and experimental fetal cardiac interventions are described.